2015
DOI: 10.1016/j.jare.2013.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Roles of dehydrin genes in wheat tolerance to drought stress

Abstract: Physiological parameters and expression levels of drought related genes were analyzed in early vegetative stage of two bread wheat cultivars (Sids and Gmiza) differ in drought tolerance capacity. Both cultivars were imposed to gradual water depletion started on day 17 till day 32 after sowing. Sids, the more tolerant cultivar to drought showed higher fresh and dry weights than the drought sensitive genotype, Gmiza. Under water stress, Sids had higher membrane stability index (MSI), lower accumulated H2O2 and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…Karak showed the highest DHN15.1 expression level among the tested landraces, on the other hand, Ramtha showed the lowest. The up regulation of DHN expression level in drought tolerant genotypes compared to drought sensitive ones under drought stress conditions in the present study is in agreement with Hassan et al (2015). Stress factors that affect plant growth are associated with plant cell dehydration.…”
Section: Discussionsupporting
confidence: 91%
“…Karak showed the highest DHN15.1 expression level among the tested landraces, on the other hand, Ramtha showed the lowest. The up regulation of DHN expression level in drought tolerant genotypes compared to drought sensitive ones under drought stress conditions in the present study is in agreement with Hassan et al (2015). Stress factors that affect plant growth are associated with plant cell dehydration.…”
Section: Discussionsupporting
confidence: 91%
“…In addition play important roles in different kinds of environmental stress conditions, such as heat and drought, low, and high temperatures and salinity . Several studies demonstrated an increase of plant HSP under different stress conditions, indicating an enhanced need for protein protection under drought stress . We found several HSPs (D6C500, Contig26564, Contig1511, IPR013126) increased in Messire and P665 in response to drought (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…LEA proteins are thought to function in many ways including stabilizers of membranes and proteins and antioxidants to protect cells from damage [47]. In response to water deficit, the expression of these genes is higher in wheat tolerant cultivars compared to sensitive ones [48]. In this study, six out of the top 25 induced genes in resistant genotypes at 6 h (5% of the DEGs) encode LEA proteins in addition to two other dehydrin-type of LEAs (Table 3).…”
Section: Cryo-protectantmentioning
confidence: 65%